Outcome After Admission in a Surgical Intensive Care Unit: Length of Stay, Mortality and Quality of Life - Abelha,Fernando (2007)
Outcome in intensive care can be categorized as mortality-related or morbidity-related. Hospital mortality is a relevant and objective endpoint. However, it is an insufficient indicator of Intensive Care unit (ICU) outcome and morbidity, disability and quality of life after discharge must also be taken into account. ICU length of stay (LOS) is often used as a surrogate for patient morbidity. Prolonged ICU stay can adversely affect prognosis by increasing the risk of complications such as infection and possibly, mortality. The study of quality of life after hospital discharge is increasingly used and accepted as a relevant measure of ICU outcome and appears as an important consideration when evaluating treatment benefits and resource allocation. It is important to understand quality of life in specific ICU subpopulations of critical ill patients and patients scheduled for elective surgery are of particular interest due to the individual risk of surgical procedures which may affect outcome.